PENGEMBANGAN E-MODUL BERBASIS PENDEKATAN MATEMATIKA REALISTIK UNTUK PESERTA DIDIK KELAS XII SMA - Monalisa Pratiwi (Departemen Matematika, 2021)
This study aims to develop e-modules based on Realistic Mathematics Education for students of class XII SMA that are valid and practical. The research was conducted at SMA Negeri 1 Koto Baru, Dharmasraya in class XII IPA 2 and XII IPA 3. The type of research is Research and Development with the Plomp model which goes through two stages, namely preliminary research and prototyping phase. The preliminary research stage consists of four analyzes, namely needs analysis, student analysis, curriculum analysis and concept analysis. The prototyping phase consists of prototype 1, prototype 2, prototype 3 and prortype 4. The results showed that the PMR-based e-module can be categorized as valid and practical. Based on the results of the validation by the validator, the PMR-based e-module meets the very valid category with a validity level of 89.22%. Then based on research, PMR-based e-modules can be categorized as very practical with a practicality level of 92.2% by students and 96.93% by educators. Keywords - E-module, Realistic Mathematics Education, Valid, Practical